Bacteriological Quality of Raw Cow Milk Obtained from Fulanis Within University of Abuja Environment - Abdulgafar Omeiza Zubair; Jemilat Oyiza Zubair; Rofiat Oyine Muhammed (Biology, Medicine, & Natural Product Chemistry, 2026)
Milk is a highly nutritious food that can serve as a suitable medium for microbial growth if not properly handled. This study assessed the bacteriological quality of raw cow milk obtained from Fulani herders within the University of Abuja environment with emphasis on the prevalence of bacterial species and their potential public health implications. Twenty raw milk samples were collected and analyzed using standard microbiological techniques, including serial dilution and spread plate methods for enumeration, determination of total bacterial load and total coliform count, Gram staining and biochemical identification. Five bacterial species were isolated; Bacillus spp. (34.29%), Lactobacillus spp. (28.57%), Staphylococcus aureus (17.14%), Pseudomonas aeruginosa (11.43%) and Escherichia coli (8.57%). The total bacterial load ranged from 5.5 × 108 to 1.15 × 109 CFU/mL, while total coliform counts ranged from 3.35 × 105 to 8.40 × 105 CFU/mL. The predominance of Gram-positive bacteria such as Bacillus and Lactobacillus reflects the natural microbial flora of raw milk, whereas the presence of Staphylococcus aureus, Pseudomonas aeruginosa and Escherichia coli indicates contamination from handlers, equipment or the environment. These findings reveal significant microbial contamination and associated public health risks linked to raw milk consumption. The study underscores the need for improved hygienic practices during milking, handling, and storage to reduce contamination and ensure consumer safety.